ELASTISITAS KESEMPATAN KERJA DAN PRODUKTIVITAS SEKTOR PERTANIAN DI SULAWESI TENGGARA TAHUN 2010-2019 - Astri Rahmadani Syam; Muhammad Syarif; Tajuddin Tajuddin (Universitas Halu Oleo, 2021)
This study aims to (1) determine the employment opportunity elasticity of the Southeast Sulawesi agricultural sector in 2010-2019, (2) to determine the development of productivity in the Southeast Sulawesi Agricultural Sector in 2010-2019. The data used in this study are secondary data, sourced from Central Bureau of Statistics (BPS) Southeast Sulawesi. The analytical tool used in this research is descriptive analysis. Based on the analysis, it can be concluded that, (1) The development of the elasticity of employment in the agricultural sector has fluctuated with an average elasticity of 9.85 percent. (2) The development of labor productivity also fluctuated with an average of 38.397 percent.